SEQUENTIAL RESPONDING IN ACCORDANCE WITH TEMPORAL RELATIONAL CUES: A COMPARISON OF BEFORE AND AFTER. - Hyland, John M.; O'Hora, Denis P.; Leslie, Julian C.; Smyth, Sinéad (Psychological Record)
The current study investigated the relative effects of Before and After relational cues on temporal order judgments. In Experiment 1, participants (N = 20) were exposed to a 5-phase temporal relational responding task. Participants observed a sequence of 2 familiar shapes and then completed either a Before or an After statement to describe the sequence. Response speeds were significantly faster for Before statements than for After statements. Experiment 2 (N = 24) extended Experiment 1, using abstract rather than familiar stimuli, and replicated the findings. The current data extend previous research, which employed temporal relational responding tasks as a measure of cognitive abilities such as intelligence, by focusing on differences in speed between responding in the presence of relational cues used in such tasks. The differences in response speeds observed between Before and After cues suggest that more work is needed to understand the specific processes that underpin such responding.